Representing black African women in The Woman King (2022): Reframing orientalist stereotypes in Hollywood cinema - Intan Nurfauziah; Krisna Sujiwa (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study examines how Black African women are represented in The Woman King (2022) and how the film reframes Orientalist stereotypes in Hollywood cinema. In this study, reframing refers to shifting the representation of Black African women from Orientalist “Others” often portrayed as inferior, exotic, passive, or dependent into active subjects with agency, authority, and leadership. Grounded in Edward Said’s concept of Orientalism and supported by Ida Rochani Adi’s media analysis approach, this qualitative study analyzes the narrative and visual strategies used in the film to construct African women’s representation. The data source is The Woman King (2022), consisting of dialogue excerpts, character actions, and visual framing from eight purposively selected key scenes presented in Pictures 1–11 with timestamps. Scenes were selected based on three criteria: (1) scenes foregrounding the Agojie’s autonomy and leadership, (2) scenes rejecting the White Savior narrative through African-initiated strategy and rescue, and (3) scenes challenging colonial power relations through resistance to tribute demands and slave trading violence. Data were collected through repeated viewing, scene documentation, and dialogue transcription. The analysis involved the matic coding and interpretation through Orientalism and colonial gaze frameworks. The findings show that The Woman King portrays Black African women as militarily competent, politically assertive, and emotionally legitimate subjects, thereby challenging Hollywood representations that position African women as marginalized or dependent on Western intervention.